DEVELOPING “BEBERAN” GAME BOARD AS AN INNOVATIVE MEDIA TO IMPROVE STUDENTS’ SPEAKING SKILLS OF PRE-SERVICE TEACHERS OF ISLAMIC ELEMENTARY EDUCATION - Herman Khunaivi (Al-Bidayah : jurnal pendidikan dasar Islam, 2021)
This study aimed to develop a “Beberan” game board as a practical, efficient, and innovative media to improve students’ speaking skills. It was carried out using the research and development method by applying Borg, Gall, and Sugiyono theories. Furthermore, it involved seven steps: analysis, designing product, preliminary test, experts’ judgments, product revisions, field test, and final product of media. A total of 30 students of the pre-service teacher study program of the Islamic elementary education, Al-Anwar Islamic College, were the subjects. The instruments used were observation, interview, and test. Based on the data obtained, the results showed that developing the “Beberan” game board as an innovative media improved students’ speaking skills at the beginner level. This improvement was observed in the result obtained from the pre-test and post-test scores, which increased from 67.867 to 72.133.